Vibration isolator carrying atomic force microscope's head. (June 2017) - Ito, Shingo; Unger, Severin; Schitter, Georg
Abstract: For high-resolution imaging in harsh environments this paper proposes a vibration isolation system that actively positions the head of an atomic force microscope (AFM) to maintain the vertical distance to the sample. On the moving platform carrying the AFM head, a displacement sensor is installed to detect the vibrations between the probe and the sample that impair the imaging quality. The detected vibrations are rejected by vertically moving the platform with feedback control. For the motion, flexure-guided Lorentz actuators are designed, such that the resulting suspension mode occurs around the major spectrum of the floor vibrations. By feedback control design, the high gain of the suspension mode is used to increase the open-loop gain for better vibration rejection. The experimental results demonstrate that the vibration isolation system can reject 99.3% of the vibrations. As a result, AFM imaging of nanoscale features is successfully performed in a vibrational environment.